An investigation of knowledge, attitude and practice of occupational safety and health (OSH) on safety climate at workplace in manufacturing industry - Nuruzzakiyah, Mohd Ishanuddin; Ezrin Hani, Sukadarin; Hanida, Abdul Aziz; Junaidah, Zakaria (National Institute of Occupational Safety and Health (NIOSH), 2019)
To investigate the safety climate and knowledge, attitude and practice (KAP) on occupational safety and health (OSH)in the manufacturingindustry, also to determine the association between safety climate factors and KAP of safety among manufacturing worker. A cross-sectional study was conducted among 59 respondents from two manufacturing plants located in Gebeng, Kuantan, Pahang. Most of the respondents were Malay (91.5%) and male (96.6%). Participants were administered a set of questionnaires (Cronbach alpha=0.674) that measured the safety climate as perceived by the workers towards their supervisor and KAP of the workers regarding safety-related matters at the workplace. Self-administered questionnaires consisted of 5 points Likert scale used to measure each of the items of safety climate and KAP. The scales for safety climate and KAP were probed using 16 items and 17 items in the questionnaires, respectively. The results were analysed using a non-parametric test, which is Spearman’s rho correlations and descriptive statistics. Bivariate analysis was performed. There was a moderate positive correlation between safety climate and KAP domains (Spearman’s rho: 0.581, p<0.01). Safety climate in the manufacturing plant is associated with KAP of the workers, thus KAP could affect the safety climate in the manufacturing plants.